Pacemaker implantation in a COVID‐19 patient. Balancing the patient's needs and the team's risk of exposure. Issue 1 (14th December 2020) - Ignatiuk, Barbara; Baratto, Fabio; Monticelli, Jacopo; Bacchion, Francesco; Marchese, Giuseppe Maria; Pasquetto, Giampaolo
Abstract : COVID‐19 patients may have cardiovascular complications requiring invasive treatment. Pacemaker implantation procedure may be challenging because of the necessity of personal protective equipment use. We report pacemaker implantation in a 78‐year‐old man with severe bilateral COVID‐19 interstitial pneumonia, a second degree 2:1 atrioventricular block, and concomitant aortic stenosis.